Using Compound Exercises (Skill) with Auditory and Visual Means And Their Effect on Some Fundamental Skills In Futsal For Women - Qassim, Sabah (Journal of Physical Education, 2016)
The aim of the research is to identify the effect of using compound exercises using auditory and visual means on some basic skills in futsal. The researchers hypothesized significant statistical differences between pre and posttests in controlling and experimental group in favor of posttest of the experimental group. The researchers used the experimental method. The subjects were (12) female futsal players from Blademn club. The subjects were divided into two equal groups; (6) controlling and (6) experimental. The researchers concluded that the experimental group developed in basic skills more than the controlling group.